Motivations for FDI and domestic capital formation - Hejazi, W; Pauly, P (Journal of International Business Studies, 2003)
Changing patterns of foreign direct investment (FDI) stock have raised important questions about their impact on domestic economies. For example, it is often thought that increased inward FDI contributes to domestic capital formation, whereas increased outward FDI reduces it. We demonstrate that such generalizations are inappropriate. We develop hypotheses linking the impact of FDI to the underlying motivation for investment. These hypotheses are tested using available Canadian industry-level data. The implication of our results is that rapid growth in outward FDI, relative to inward growth, should not be considered as a negative development, and may reflect success.